ISO 9000 AND THE SYSTEM FOR QUALITY MANAGEMENT - Flores Konja, Adrián Alejandro (2014)
In the present article, the result of exploratory re-search is part of an ongoing investigation, sponsored by Vice President for Research of UNMSM and with the support of the Research Institute of Accounting and Financial Sciencesat the Faculty of Accounting, proposed that the elements should be considered in a System of quality Management, appropriate to a Postgraduate Unit, which is a requirement under the accreditation of the quality of education, according to the quality model of CONEAU.System Quality Management as such, contains a co-herent organization with different systems formulated under the Quality Model of CONEAU interconnected systems related to the 3 dimensions (management, training and support services to professional training), in which the core systems of curriculum planning.This system for the accreditation of the Postgraduate Unit in accordance with the ISO 9000 standard is analyzed because of their consistency with Quality Model of CONEAU and proposes general quality policies deemed appropriate for Unit Graduate School of Accounting.